Management of guillain-barré syndrome patients with type 2 respiratory failure in RSUD Gambiran - Perwirayuda, Bima (ARKA INSTITUTE, 2024)
Guillain-Barré syndrome (GBS) is an autoimmune disorder that affects the peripheral nervous system. Most patients with GBS are clinically characterized by tetraplegia with or without sensory disturbances. In GBS this is due to a hyperreactive immune response including the release of anti-ganglioside antibodies, the formation of antibody-dependent immune complexes, and an increase in macrophages that cause demyelination and axonal degeneration. In severe cases GBS can appear clinically progressive with respiratory muscle involvement requiring mechanical ventilation and treatment in the intensive care unit. The patient we report is a 24 year old man with clinical type 2 respiratory failure with suspicion of GBS who was initially examined at the RSUD Kilisuci, then referred to the RSUD Gambiran and treated in the ICU at the RSUD Gambiran and received immunomodulatory therapy in the form of plasma exchange (PE). The patient was treated for 10 days in the ICU at RSUD Gambiran with the outcome being that the patient was able to move to the ward.